External validation of a non-invasive vaginal tool to assess the risk of intra-amniotic inflammation in pregnant women with preterm labor and intact membranes - Cobo, Teresa; Burgos-Artizzu, Xavier P; Ferrero, Silvia; Balcells, Judith; Bosch, Jordi; Gené, Amadeu; Murillo, Clara; Rueda, Claudia; Boada, David; Sánchez-Antón, Maria Teresa; Kacerovsky, Marian; Jacobsson, Bo; et al. (Journal of perinatal medicine, 2025)
OBJECTIVES: To prospectively validate the diagnostic performance of a non-invasive point-of-care tool (Rapid IAI System), including vaginal alpha-fetoprotein and interleukin-6, to predict the occurrence of intra-amniotic inflammation in a Spanish cohort of patients admitted with a diagnosis of preterm labor and intact membranes. METHODS: From 2017 to 2022, we prospectively evaluated a cohort of pregnant women diagnosed with preterm labor and intact membranes admitted below 34+0 weeks who underwent amniocentesis to rule-in/out intra-amniotic infection and/or inflammation. Vaginal sampling was performed at the time of amniocentesis or within 24-48 h. Amniotic fluid IL-6, vaginal alpha-fetoprotein and vaginal IL-6 concentrations were measured using a point-of-care tool provided by Hologic Inc., "Rapid IAI System". We defined intra-amniotic inflammation when amniotic fluid IL-6 values were greater than 11.3 ng/mL. During recruitment, clinicians were blinded to the results of the point-of-care tool. The original prediction model proposed by Hologic Inc. to predict intra-amniotic inflammation was validated in this cohort of patients. RESULTS: We included 151 patients diagnosed with preterm labor and intact membranes. Among these, 29 (19.2 %) had intra-amniotic inflammation. The algorithm including vaginal IL-6 and alpha-fetoprotein showed an area under curve to predict intra-amniotic inflammation of 80.3 % (±5.3 %) with a sensitivity of 72.4 %, specificity of 84.6 %, positive predictive valuve (PPV) of 52.5 %, negative predictive value (NPV) of 92.9 %, and a positive likelihood ratio (LR+) of 4.6 and negative likelihood ratio (LR-) of 0.33. CONCLUSIONS: External validation of a non-invasive rapid point-of-care tool, including vaginal alpha-fetoprotein and IL-6, showed very good diagnostic performance for predicting the absence of intra-amniotic inflammation in women with preterm labor and intact membranes.
Keywords: dospělí; chorioamnionitida; Chorioamnionitis; hodnocení rizik; Female; vaginal alpha-fetoprotein; preterm labor and intact membranes; biologické markery; Amniocentesis; alpha-Fetoproteins; Biomarkers; Adult; ženské pohlaví; Vagina; prediction models; lidé; těhotenství; předčasná porodní činnost; Interleukin-6; Risk Assessment; intra-amniotic inflammation; prospektivní studie; amniocentéza; Prospective Studies; alfa-fetoproteiny; Amniotic Fluid; plodová voda; interleukin-6; Point-of-Care Systems; point-of-care; vyšetření u lůžka; Obstetric Labor, Premature; vaginal interleukin-6; Pregnancy; vagina; Humans